The Measure of Online Disinhibition (MOD): Assessing perceptions of reductions in restraint in the online environment. (January 2021) - Stuart, Jaimee; Scott, Riley
Abstract: Online disinhibition, or the experience of diminishing constraints when online, has important influences on behavior, yet theoretically robust, reliable, and valid measures of this construct are lacking. This research developed a new Measure of Online Disinhibition (MOD). In study 1, 403 participants were split into two samples; n = 212 were subject to exploratory factor analysis, and n = 191 to confirmatory factor analysis. The final 12 items loaded onto a single factor with high reliability and construct validity among a range of measures (toxic and benign disinhibition, time online, false self, online self-disclosure, and trolling). In Study 2, using a distinct sample (N = 242), the MOD was again confirmed and the nomological network was extended to examine cyberbullying and well-being. Additionally, in both studies path models were tested to explore the mediation of time online on positive and negative indicators via MOD. Results found that greater time online was associated with increases in both positive and negative cyber behaviors but decreased well-being via increases in MOD. The MOD operationalizes online disinhibition in a theoretically driven fashion, allowing researchers to build upon our understanding of the impacts of the online environment on human behavior in a systematic way. Highlights: Two studies developed and validated the Measure of Online Disinhibition (MOD). The MOD overcomes many limitations within existing online disinhibition measures. Increases in internet and social media use significantly predicted greater MOD. Higher MOD increased reported engagement in positive and negative online behaviors. Higher MOD predicted decreases in flourishing, an indicator of well-being.